A Novel Electrospun Nano-fabric Graft Allows Early Cannulation Access and Reduces Exposure to Central Venous Catheters. Issue 3 (July 2013) - Karatepe, Celalettin; Altinay, Levent; Yetim, Tulin Durgun; Dagli, Celalettin; Dursun, Suat
Purpose: The use of tunneled central venous catheters (CVC) as vascular access for hemodialysis treatment is increasing worldwide. We present a novel polycarbonate urethane nano-fabric graft, produced by electrospinning technology, which has self-sealing features that avoid seroma formation and allow puncturing within 48 hours. The aim of this study was to assess its advantages in a setting where late referral is common. Methods: A retrospective single center study assessed 24 implanted grafts in 24 patients with maximal follow-up of 18 months; patency rates, time to first cannulation and post-operative complications were assessed. Results: Successful access was achieved in all 24 patients within 48 hours. In 50% of the patients cannulation was performed within 24 hours without increasing the complication rate. Twelve month primary and secondary patencies were 50% and 70.8%, respectively. Excluding early failures (within 30 days) because of surgical problems, 12 month primary and secondary patencies were 75% and 81.2% respectively. Complication and infection rates were 10.94 and 0.49/1000 dialysis procedures, respectively. No pseudoaneurysms or seromas were documented at 18 months. Conclusions: Early cannulation was successful in all patients with good 12-month primary and secondary patency rates, compared to data reported by others on polytetrafluoroethylene (PTFE) grafts. The infection rate was substantially lower than in tunneled CVCs. Therefore, the AVflo graft may improve the clinical status of dialysis patients by decreasing the exposure to CVCs.